2014
DOI: 10.1088/1742-6596/488/3/032030
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond Transient Absorption Spectroscopy of doubly-excited states in helium

Abstract: Strong-field manipulation of autoionizing states is a crucial aspect of electronic quantum control. Recent measurements of the attosecond transient absorption spectrum of helium dressed by a fewcycle visible pulse [Ott et al., arXiv:1205.0519[physics.atom-ph] ] provide evidence of novel ultrafast resonant phenomena, namely, two-photon Rabi oscillations between doubly-excited states and the inversion of Fano profiles. Here we present the results of accurate ab-initio calculations that agree with these observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 103 publications
1
9
0
1
Order By: Relevance
“…This protocol resembles the attosecond transient absorption employed to time-resolved core-level dynamics [37]. In fact, Pfeifer and co-workers [101] recently implemented the attosecond transient absorption analog of this experimental scheme and, indeed, interference fringes similar to those described here were observed and theoretically confirmed by one of us with full ab initio simulations [102].…”
Section: B Time-resolved Autoionization Resonances In Heliumsupporting
confidence: 63%
“…This protocol resembles the attosecond transient absorption employed to time-resolved core-level dynamics [37]. In fact, Pfeifer and co-workers [101] recently implemented the attosecond transient absorption analog of this experimental scheme and, indeed, interference fringes similar to those described here were observed and theoretically confirmed by one of us with full ab initio simulations [102].…”
Section: B Time-resolved Autoionization Resonances In Heliumsupporting
confidence: 63%
“…Very recently, the experimented reported by Ott et al 30 , in which the ultrafast TAS of Helium displayed characteristic beyond-SAE features, was theoretically analyzed in Ref. 31, utilizing an exact solution of the time-dependent Schrödinger equation, that cannot however be easily extended to larger systems. Finally, the above-mentioned experiment of Goulielmalkis et al 22 was analized with the model described in Ref.…”
mentioning
confidence: 99%
“…The relative phase of the interfering pathways can be manipulated with a moderately strong NIR pulse, which enables control over the exact Fano line shape. A theoretical analysis revealed that the inversion of the Fano profile observed at a particular NIR intensity is expected to periodically repeat itself as a function of further increasing intensity [19].…”
Section: Review Of Recent Experimentsmentioning
confidence: 99%